Taxonomic study of the Eucarpiini (Hemiptera: Fulgoromorpha: Cixiidae) from China - Chen, Xiang-Sheng; Zhi, Yan (Zootaxa, 2023)
The Chinese cixiid planthopper tribe Eucarpiini is studied taxonomically. Four genera and 29 species belonging to Eucarpiini are reported from China, including 15 new species of three genera: Dilacreon (Dilacreon) deltodontus sp. nov., Dilacreon (Eluzalmon) apiculatus sp. nov., D. (E.) arcuatus sp. nov., D. (E.) biprocessus sp. nov., D. (E.) congjiangensis sp. nov., D. (E.) distentus sp. nov., D. (E.) erectus sp. nov., D. (E.) falcatus sp. nov., D. (E.) parapentagonus sp. nov., D. (E.) transversus sp. nov., Kirbyana projecta sp. nov., K. spinata sp. nov., Neocarpia brevispina sp. nov., N. longispina sp. nov. and N. trispina sp. nov.. All species dealt with are described and illustrated and keys for genera and their species are also given.